Adaptive Fuzzy-Based Energy and Delay-Aware Routing Protocol for a Heterogeneous Sensor Network - Mothku, Sai Krishna; Rout, Rashmi Ranjan (Journal of Computer Networks and Communications, 2019)
In a heterogeneous sensor actor network, packet loss may occur due to bad link quality, overflow of buffer, and low energy levels. Retransmission of the lost packets leads to more energy consumption and delay. Ensuring data reliability and minimum delay requirement while improving energy efficiency are challenging issues in a resource-constrained heterogeneous sensor actor network. In this paper, a fuzzy-based delay and energy-aware intelligent routing mechanism has been proposed to select efficient routes. In the proposed mechanism, routing decisions are taken using a fuzzy logic system by considering network resources, such as residual energy, quality of link, available buffer size, and distance (proximity). In a network, a node with higher residual energy, higher free available buffer, good link quality, and close distance (proximity) gets opportunity to become a next hop node in a routing path. Furthermore, network performance has been analyzed with various network states. Simulation has been carried out using Network Simulator 3 by considering performance metrics, such as delay, number of retransmissions, energy consumption, lifetime, and network stability of the network.